2023
DOI: 10.1159/000528861
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of NT-proBNP and Procalcitonin during Continuous Venovenous Hemodialysis with the Medium Cutoff Filter in Patients with Rhabdomyolysis-Associated Early Acute Kidney Injury

Abstract: <b><i>Introduction:</i></b> In polytrauma patients with AKI continuous venovenous hemodialysis (CVVHD) with medium cutoff membrane filters is commonly adopted to increase the removal of both myoglobin and inflammatory mediators, but its impact on increasing molecular weight markers of inflammation and cardiac damage is debated. <b><i>Methods:</i></b> Twelve critically ill patients with rhabdomyolysis (4 burns and 8 polytrauma patients) and early AKI requiring CVV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…As a result, we experienced both a high number of hemorrhagic episodes and premature circuit clotting. In effect, in agreement with previous reports [ 8 , 26 , 27 ], we observed that the safety of the treatment was significantly increased with citrate, as documented by a significant reduction in hemorrhagic complications and an increased daily hour of effective dialysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a result, we experienced both a high number of hemorrhagic episodes and premature circuit clotting. In effect, in agreement with previous reports [ 8 , 26 , 27 ], we observed that the safety of the treatment was significantly increased with citrate, as documented by a significant reduction in hemorrhagic complications and an increased daily hour of effective dialysis.…”
Section: Discussionsupporting
confidence: 93%
“…CKRT was performed according to the manufacturer’s instructions with high permeability biocompatible synthetic dialysis membranes (polyacrylonitrile or polysulfone dialyzers). For the patients with documented rhabdomyolysis requiring CKRT, from 2011 our protocol envisaged the use of a medium cut-off polysulfone filter EMiC2 (Fresenius Medical Care) to increase the myoglobin loss in the effluent [ 27 ]. Blood flow and effluent rates were set according to the target of dialysis adequacy, accomplishing the dialysis target of 20–25 mL/kg/h [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data from our research group already showed a better myoglobin clearance in patients treated with CVVHD-HCO compared to CVVHDF (mean difference of 5.5 (4–7) ml/min, p < 0.0005; (12.3 vs. 3.7 ml/min)) [ 12 ]. Another investigation could verify a relevant myoglobin elimination in CVVHD-HCO in rhabdomyolysis, too [ 48 ]. In a recently published study CVVHD-HCO combined with an adsorber had a particularly good elimination capacity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal treatment can not recommended in patients with working kidneys [43] as it provides the highest elimination capacity of myoglobin. If KRT is necessary, various modalities of KRT with different myoglobin elimination capacity are available [9,11,12,14,15,17,21,32,[46][47][48], but good clinical data concerning outcome of patients are missing. Therefore, no recommendation for any specific method of KRT is available until now [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation